'Handing over to the patient': A FRAM analysis of transitional care combining multiple stakeholder perspectives. (May 2020) - O'Hara, Jane K.; Baxter, Ruth; Hardicre, Natasha
Abstract: Introduction: The period following discharge can present risks for older adults. Most research has focused on hospital discharge with less attention paid to on-going care needs. Despite evidence that patients undertake 'invisible work' to improve care safety, their reported willingness to be involved in care, and the consensus that successful transitions interventions include patient involvement, in reality, this is variable. Further, little research has viewed transitional care as a 'system', with gaps, interdependencies and variability across settings, nor the role of patients and families in supporting the system resilience. Research objectives: 1) model transitional care from multiple perspectives using the Functional Resonance Analysis Method (FRAM); 2) use the model to develop a theory of change to support intervention development. Method: We drew data from two studies: i) exploring the perspective of older adults across transitional care, and ii) exploring how health services experience transitional care. We employed the FRAM to develop a model of transitional care, with a system boundary spanning an older patient's admission to hospital, through to thirty days post-discharge. Findings: Modelling transitional care from multiple perspectives was challenging. 27 functions were identified with interdependencies between hospital-based functions and patient-led functions once home, the success of which may impact on transitions 'outcomes' (e.g. safety events, readmissions). The model supported development of a theory of change, to guide future intervention development. Conclusions: Supporting certain patient-facing upstream hospital functions (e.g. encouraging mobility, supporting a better understanding of medication and condition), may lead to improved outcomes for patients following hospital discharge.